Key success factors of online food ordering services: an empirical study - Kedah, Zulkarnain; Ismail, Yusof; Haque, A. K. M. Ahasanul; Ahmed, Selim (Malaysian Institute of Management, 2015)
This study examines the determinants of the customer ordering experience, which include website trust, customer satisfaction and loyalty. The determinants are represented by website quality and service quality. A survey data of 353 online food ordering customers were used to test the research model using structural equation modelling (SEM). Results reveal that not only is there a significant positive relationship between website quality and website trust but also a significant positive relationship between service quality and customer satisfaction. Furthermore, significant positive relationships are also found not only between website trust and customer satisfaction but also between customer satisfaction and loyalty. Finally, the study also found an unexpected direct link between service quality and loyalty. Overall, the study provides valuable insights for operating online food ordering services successfully.